The existence and nonexistence of entire large solutions for a quasilinear Schrödinger elliptic system by dual approach - Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong; Cui, Y. (Academic Press, 2018)
© 2018 Elsevier Inc. In this paper, we establish some new results on the existence and nonexistence of radial large positive solutions for a modified Schrödinger system with a nonconvex diffusion term by a successive iteration technique and the dual approach. The necessary and sufficient condition for the existence of radial large positive solutions is established. Our results improve and extend many previous work in this field of research.